2012 International Conference on Field-Programmable Technology 2012
DOI: 10.1109/fpt.2012.6412113
|View full text |Cite
|
Sign up to set email alerts
|

A high speed open source controller for FPGA Partial Reconfiguration

Abstract: Partial Reconfiguration (PR) is an advanced technique, which improves the flexibility of FPGAs by allowing portions of a design to be reconfigured at runtime by overwriting parts of the configuration memory. PR is an important enabler for implementing adaptive systems. However, the design of such systems can be challenging, and this is especially true of the configuration controller. The generally supported methods and IP have low throughput, resulting in long configuration time that precludes PR from systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 12 publications
0
34
0
Order By: Relevance
“…Previous experiments with traditional FPGAs showed that a custom solution can provide near theoretical peak reconfiguration throughput [2]. But such custom controllers were designed for non-processor systems, and hence did not provide a software-centric view or run-time reconfiguration management, making them difficult to port to the Zynq.…”
Section: B Zycap Pr Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous experiments with traditional FPGAs showed that a custom solution can provide near theoretical peak reconfiguration throughput [2]. But such custom controllers were designed for non-processor systems, and hence did not provide a software-centric view or run-time reconfiguration management, making them difficult to port to the Zynq.…”
Section: B Zycap Pr Managementmentioning
confidence: 99%
“…Currently supported methods of PR management on the Zynq fail to address this issue. Our previous work demonstrated that custom reconfiguration controllers can considerably reduce reconfiguration overhead in non-processor based systems [2]. In this paper, we present a new open-source reconfiguration controller and associated driver that significantly improve reconfiguration throughput in the Zynq while freeing the processor to work on other tasks.…”
Section: Introductionmentioning
confidence: 99%
“…DPR significantly improved reconfiguration performance [13], however the efficiency of the traditional design approach for DPR is heavily impacted by how a design is partitioned and floorplanned [14], tasks that require FPGA expertise. Furthermore, the commonly used configuration mechanism is highly sub-optimal in terms of throughput [15]. Despite numerous efforts in reducing reconfiguration times and improving CAD tool support for dynamic reconfiguration of FPGA fabric [16], [13], the implementation of rapidly reconfigurable hardware accelerators is still difficult.…”
Section: B Reconfiguration Latencymentioning
confidence: 99%
“…For example, in [8], a L4 kernel is ported to manage hardware and software tasks, but without using dynamic reconfiguration. In parallel, research in [9] discussed the reconfiguration management on Zynq platform at the application level, without using any operating system and thus with poor flexibility.…”
Section: Related Workmentioning
confidence: 99%